The Existence of Traditional Madurese Batik Patterns in the Exposure of Time and Technology - Lulus Sugeng Triandika (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2024)
Batik is generally inspired by cultural elements and philosophies of life. Madura Batik as part of Indonesian Batik continues to maintain its existence from generation to generation. However, the influence of developments over time and technological innovation has brought new things to Madurese Batik. On the one hand, batik is increasingly popular in society, but on the other hand, concerns arise regarding the originality of batik patterns. This phenomenon is thought to have an impact on the existence of traditional batik patterns that have existed for hundreds of years in the archipelago. Batik is interesting to study as a cultural entity that is expected to maintain ancestral rules in the process of making it. Even though there are many articles about batik, there are still few discussions about batik patterns. So, this article has urgency in enriching literacy about batik patterns. In this article, data was obtained through observation, literature articles, and interviews with batik makers, then conclusions were drawn based on data analysis. The result is the emergence of modern batik patterns because of market demand. This impacts the existence of traditional Madurese Batik patterns which are increasingly being displaced by contemporary batik patterns. Another fact is the existence of printed batik which has an impact on the existence of traditional batik houses. Traditional batik patterns will become increasingly rare and will be forgotten or even lost.   Batik secara umum terinspirasi dari unsur budaya dan filosofi kehidupan. Batik Madura sebagai bagian dari Batik Nusantara terus dijaga keberadaannya turun-temurun lintas generasi. Namun, pengaruh perkembangan zaman dan inovasi teknologi menghadirkan hal-hal baru di batik Madura. Dalam satu sisi batik semakin populer di masyarakat, namun di sisi lain muncul keprihatinan terkait orisinalitas corak batik. Fenomena tersebut dianggap berimbas pada eksistensi corak batik tradisional yang telah ada sejak ratusan tahun di nusantara. Batik menarik untuk dikaji sebagai entitas budaya yang diharapkan mempertahankan tata aturan leluhur dalam proses pembuatannya. Meskipun telah banyak artikel tentang batik, namun masih sedikit membahas tentang corak batik. Sehingga artikel ini memiliki urgensi dalam memperkaya literasi tentang corak batik. Dalam artikel ini data diperoleh melalui observasi, artikel literatur, dan wawancara dengan pembatik, kemudian diambil kesimpulan berdasar analisis data. Hasilnya adalah munculnya corak batik modern sebagai imbas permintaan pasar. Sehingga berdampak pada eksistensi corak tradisional Batik Madura yang semakin tergeser corak batik komtemporer. Fakta lain adalah Keberadaan batik printing yang berdampak pada eksistensi rumah batik tradisional. Corak batik tradisional akan semakin jarang dibuat sehingga terlupakan atau bahkan hilang.